Nurses' Experiences Confirmed Positive Covid-19: Qualitative Study - Faqih Ruhyanudin; Sunardi Sunardi; Hafidz Shofi Fuad Efendi; Nadila Rosi Azalia (Universitas Muhammadiyah Semarang, 2022)
Coronavirus Disease 2019 (Covid-19) has become a global pandemic worldwide, and the number of incidents increases every day. Nurses who provide care services in contact with patients are a vulnerable group with a high risk of transmission, so it is not uncommon for nurses to feel anxious and afraid to provide patients. This study describes the experiences of nurses who were confirmed COVID-19, including the origin of the exposure, clinical manifestations, the healing efforts made, and their psychological and spiritual experiences. The research design used was qualitative with a phenomenological approach to clinical nurses who had been confirmed positive for COVID-19 and at the time of the study had been declared cured—collecting data using semi-structured in-depth interviews with participants selected by purposive and snowball sampling techniques. This study reached saturation in the sixth participant—data analysis with Colaizzi Measures. The study identified six themes: 1) Lack of courage to report symptoms and carry out examinations, 2) Exposure to COVID-19 at their work, 3) Mild symptoms of Covid-19, 4) The most severe problem it felt was the psychological, 5) Efforts to heal with medication, 6) Support from workplace institutions and colleagues, 7) Religious, spiritual efforts, and 8) The sequelae after being healed. The negative stigma in the community towards covid survivors causes them to hide their illness so that the hospital and the surrounding community don't know about it. When confirmed COVID-19, the participants were in the mild category due to their young age and received the second vaccine. Although the symptoms are mild, they feel a psychological burden in fear and anxiety if their condition worsens. Efforts for healing use a medical approach with medication, recreational, psychological support, herbal treatment, and spiritual support in worship and prayer.